Analisis Systematic Literatur Review : Corporate University Sebagai Strategi dalam Meningkatkan Kompetensi Pegawai - Setiawati, Rini; Sutisna, Anan; Saefudin, Yetty Supriyati (Universitas Pendidikan Ganesha, 2023)
The results of this study will provide an understanding of Corporate University how it affects competence, the implementation process is and how knowledge management (KM) is in the implementation of CorpU. The research method used is SLR by identifying, analyzing, based on the results of previous research obtained through google schoolar and scopus. The search process is used to obtain relevant sources to get answer research questions (RQ). The data is in the form of secondary data, The keywords in the literature search are